2015
DOI: 10.3934/mbe.2015.12.1107
|View full text |Cite
|
Sign up to set email alerts
|

Cilium height difference between strokes is more effective in driving fluid transport in mucociliary clearance: A numerical study

Abstract: Mucociliary clearance is the first line of defense in our airway. The purpose of this study is to identify and study key factors in the cilia motion that influence the transport ability of the mucociliary system. Using a rod-propel-fluid model, we examine the effects of cilia density, beating frequency, metachronal wavelength, and the extending height of the beating cilia. We first verify that asymmetry in the cilia motion is key to developing transport in the mucus flow. Next, two types of asymmetries between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…There are numerous reports in the literature documenting that the murine trachea is very sparsely ciliated [30–37% ( Pack et al, 1980 ; Klein et al, 2009 ; Kiyota et al, 2014 )] and that ciliated cells in the trachea are found in scattered patches ( Pack et al, 1980 ). In fact, Pack et al (1980) commented that in the murine trachea the ciliated cells “were so far apart that is difficult to envisage how such a mucous sheet would be propelled.” As it has been previously shown that there is a positive correlation between cilial density and the rate of MCC ( Smith et al, 2008 ; Xu and Jiang, 2015 ; Chatelin and Poncet, 2016 ; Leung et al, 2019 ), it is likely that the difference in the rate of MCC between the PNP and trachea is in large part a result of significantly more abundant ciliated cells in the PNP. Additionally, this likely explains the circuitous route (non-linear) that beads/mucus follows during MCC in the trachea, compared to the linear paths observed in the PNP.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…There are numerous reports in the literature documenting that the murine trachea is very sparsely ciliated [30–37% ( Pack et al, 1980 ; Klein et al, 2009 ; Kiyota et al, 2014 )] and that ciliated cells in the trachea are found in scattered patches ( Pack et al, 1980 ). In fact, Pack et al (1980) commented that in the murine trachea the ciliated cells “were so far apart that is difficult to envisage how such a mucous sheet would be propelled.” As it has been previously shown that there is a positive correlation between cilial density and the rate of MCC ( Smith et al, 2008 ; Xu and Jiang, 2015 ; Chatelin and Poncet, 2016 ; Leung et al, 2019 ), it is likely that the difference in the rate of MCC between the PNP and trachea is in large part a result of significantly more abundant ciliated cells in the PNP. Additionally, this likely explains the circuitous route (non-linear) that beads/mucus follows during MCC in the trachea, compared to the linear paths observed in the PNP.…”
Section: Discussionmentioning
confidence: 94%
“…Although mucociliary clearance (MCC) plays a critical role in maintaining health throughout the respiratory system, one might expect a more robust MCC in the nasal cavity compared to that of the lower airways. An enhanced MCC could be accomplished in several ways: (1) an increase in density of ciliated cells, (2) an elevated rate of ciliary beat frequency, both of which have been shown to increase the rate of MCC ( Smith et al, 2008 ; Sears et al, 2015 ; Xu and Jiang, 2015 ; Chatelin and Poncet, 2016 ; Leung et al, 2019 ), and (3) an “optimized” mucus layer (e.g., more favorable composition or concentration of mucins) that is more efficient at trapping deleterious inhaled substances and/or is more effectively cleared by the cilia.…”
Section: Introductionmentioning
confidence: 99%
“…As a frame of reference, the typical Re value for a swimming bacterium (e.g., E. coli in water) is in the order of 104, the smallest fish is about 1, a human swimmer is 104, and a blue whale is 4×108. The value of Re in the mammalian respiratory tract is around 0.01 [34], suggesting a dominating viscous force in the mucociliary system. Mathematically, the Navier–Stokes equations [74] make up the standard model that governs the fluid flow dynamics.…”
Section: Phylogeny Of Mathematical Models Of Mucociliary Systemmentioning
confidence: 99%
“…Xu and Jiang [34] aimed to identify key factors in the cilia motion that influence the ability of fluid transport in mucociliary clearance. In their simulations, the rod-propel-fluid model (Figure 6c) treated cilia as stiff rods that followed prescribed motions.…”
Section: Phylogeny Of Mathematical Models Of Mucociliary Systemmentioning
confidence: 99%
See 1 more Smart Citation